EVALUASI KESUKSESAN PENERAPAN SISTEM MANAJEMEN PERGUDANGAN BERBASIS APLIKASI PADA PT XYZ - Almasah Ulya Ramadhani; Nurul Hidayati; Nisa Zahra (MULTINETICS, 2025)
A warehouse management system is a database-based computer program designed to improve the efficiency of warehouse performance and to make it easier to manage the storage of goods. XYZ Store Tangerang branch is a retail business that implements an application-based warehousing management system called AIMS. Measuring the success of application implementation is necessary to see the influence of system quality, information quality, and service quality on use, user satisfaction, and net benefits. Success measurement is carried out to improve the quality and impact received from the application. This research is located in Tangerang and will be carried out in April – June 2024. Descriptive analysis and SEM PLS analysis were used to process primary research data through questionnaires distributed to 50 respondents. The results showed that system quality and service quality affected net benefits but did not affect user use and satisfaction. Meanwhile, the quality of information affects user use and satisfaction but does not affect the net benefits.